Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions

If there are (2n+1) terms in an arithmetic series then prove that the ratio of the sum f odd terms to the sum of even terms is(n+1):1



Let us consider n=1 
then we get (2n+1)= 2*1+1=3
let us consider those 3 terms be 1,2,3 
sum of the odd terms 1+3=4
sum of the even terrms =2
Now the ratio of odd terms to even terms is 4:2=2:1
which satisfy the condition (n+1):1=(1+1):1=2:1
Hence proved
0 0 0
ok i am studying 12th
what about u
I'm 10th
I just passed out 10th
The Brainliest Answer!
In AP. Let first term =a and common difference=d , Now, there are 2n+1 terms , i.e. no of terms is odd. Plz notice that in 2n+1 terms, n terms will be even while n+1 terms are odd
Now, consider the odd terms, Here, first term will be a, and common difference will be 2d
and for even numbered terms, First term will be a+d and common difference will be 2d

Now, coming to the problem, ,
Ratio of sum of odd terms to even terms= \frac{ \frac{n+1}{2}(2a+(n+1-1)d }{ \frac{n}{2}(2(a+d)+(n-1)d) }

Now, u can just simplify to see the desired ratio
1 5 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts